Effect of Reinforcing by Palms-Carbon Hybrid Fibers on Mechanical Properties of Conbextra Epoxy EP-10 Resin (Journal of University of Babylon for Engineering Sciences, 2017)
The objective of this research is to study the effect of reinforcing with different percentage (20%, 40%, and 60%) of hybrid palms-carbon fibers on mechanical properties of conbextra epoxy EP-10 resin. The aim from this incorporation of both fibers into a single matrix will stabilize mechanical properties and lowering manufacturing costs. In this research the impact strength, tensile strength, flexural strength, and hardness were studied for composite material reinforced with hybrid fibers for palms and carbon as a woven roving (0°-90°) with density (1.45g/m3). These fibers were mixed with conbextra epoxy EP-10 resin in different reinforcement percentage and studied these effects on the mechanical properties of conbextra epoxy EP-10 resin. It has shown an improvement in these mechanical properties after reinforcement by fibers where the value of mechanical properties will increase with increasing percentage of reinforcement. Impact strength increased from (23Kj/m2) to (170Kj/m2), and tensile strength from(70MPa) to (365MPa), and flexural strength from(0.162GPa) to (1.55GPa), and hardness from(8.5N/m2) to (80N/m2) for reinforcing percentages 0% and 60% respectively.